Evaluation of Growth Performance, Biochemical Composition, and Polyhydroxyalkanoates Production of Four Cyanobacterial Species Grown in Cheese Whey - Eirini Sventzouri; Konstantinos Pispas; Georgia G. Kournoutou; Maria Geroulia; Eleni Giakoumatou; Sameh Samir Ali; Michael Kornaros (Microorganisms)
Large-scale cultivation of cyanobacteria is often limited by the high cost of synthetic culture medium and the environmental impact of nutrient consumption. Cheese whey, a major agro-industrial waste product, is rich in organic and inorganic nutrients, making it a promising low-cost alternative for microbial growth while addressing waste bioremediation. This study investigates the growth performance and the biochemical composition of four different cyanobacterial species (Phormidium sp., Synechocystis sp., Chlorogloeopsis fritschii, and Arthrospira platensis), cultivated in cheese whey (CW). Pretreated CW was used at 20% and 100% v/v concentrations. All species grew satisfactorily in both concentrations, reaching biomass above 4 g L−1 (in 100% v/v CW) and 2 g L−1 (in 20% v/v CW). The highest μmax value (0.28 ± 0.02 d−1) was presented by Synechocystis sp. grown in 20% CW. Waste bioremediation of both 20 and 100% v/v CW demonstrated effective nutrient removal, with COD removal exceeding 50% for most species, while total nitrogen (TN) and total phosphorus (TP) removals reached up to 33% and 32%, respectively. Biochemical composition analysis revealed high carbohydrate and protein content, while lipid content remained below 15% in all cases. Interestingly, C. fritschii accumulated 11% w/w polyhydroxyalkanoates (PHAs) during the last day of cultivation in 20% v/v CW. These findings highlight the potential of C. fritschii as a valuable candidate for integration into bioprocesses aimed at sustainable bioplastic production. Its ability to synthesize PHAs from agro-industrial waste not only enhances the economic viability of the process but also aligns with circular economy principles. This study is a primary step towards establishing a biorefinery concept for the cultivation of cyanobacterial species in cheese whey-based wastewater streams.